Financial Support to Eligible Countries for the Switch From Trivalent to Bivalent Oral Polio Vaccine—Lessons Learned - Shendale, Stephanie (J Infect Dis, 2017)
The global switch from trivalent oral polio vaccine (tOPV) to bivalent oral polio vaccine (bOPV) (“the switch”) presented an unprecedented challenge to countries. In order to mitigate the risks associated with country-level delays in implementing the switch, the Global Polio Eradication Initiative provided catalytic financial support to specific countries for operational costs unique to the switch. Between November 2015 and February 2016, a total of approximately US$19.4 million in financial support was provided to 67 countries. On average, country budgets allocated 20% to human resources, 23% to trainings and meetings, 8% to communications and advocacy, 9% to logistics, 15% to monitoring, and 5% to waste management. All 67 funded countries successfully switched from tOPV to bOPV during April–May 2016. This funding provided target countries with the necessary catalytic support to facilitate the execution of the switch on an accelerated timeline, and the mechanism offers a model for similar support to future global health efforts, such as the eventual global withdrawal of bOPV.